Human Rights between the Prophetic Biography and the Battle of Banū Qurayẓah: A Historical and Critical Study - Dr: Sabah Hassan falah Al Badri (Journal of College of Education, 2025)
This study aims to examine the Battle of Banū Qurayẓah in light of modern human rights standards, through a critical analysis of the historical narratives and a comparative reading with the ethical and legal principles embedded in the Prophetic Sīrah (biography of the Prophet Muḥammad, peace be upon him and his family). The research proceeds from the premise that the Prophet’s handling of this crisis was neither arbitrary nor retaliatory; rather, it was grounded in a coherent moral and legal framework that remarkably aligns with what is today known as International Humanitarian Law (IHL).The study demonstrates that the widely circulated narrative depicting the event as a “mass execution” lacks definitive transmission and relies on weak and contradictory reports, often inflated in numbers. In contrast, the Qur’ānic verse - “Some you killed and some you took captive” (al-Aḥzāb 33:26) - clearly distinguishes between those guilty of active treachery and non-combatants. Consequently, punishment was confined to those who had taken up arms or directly violated the pact, while women, children, and civilians were spared.A comparative analysis reveals that the Prophetic practice anticipated key principles of modern humanitarian law, such as the protection of civilians (Geneva Conventions of 1949 and Additional Protocol I, Article 48), the right to a fair trial (Article 10, Universal Declaration of Human Rights, 1948), individual accountability, and the prohibition of collective punishment. The arbitration conducted by the Prophet through Saʿd ibn Muʿādh represents an early form of judicial independence and transitional justice as later conceptualized in modern legal thought.In conclusion, the study argues that, when properly contextualized, the Battle of Banū Qurayẓah stands as an early model of humanitarian justice in times of conflict. The Prophetic Sīrah, far from contradicting the essence of human rights, emerges as one of their earliest manifestations — balancing the rights of society to security with the rights of individuals to justice.
Keywords: Battle of Banū Qurayẓah; Human Rights; Prophetic Sīrah